Correlative Fluorescence and Scanning Electron Microscopy of Labelled Core Fucosylated Glycans Using Cryosections Mounted on Carbon-Patterned Glass Slides - Vancová, Marie; Nebesářová, Jana (PloS one, 2015)
The aim of the study is co-localization of N-glycans with fucose attached to N-acetylglucosamine in α1,3 linkage, that belong to immunogenic carbohydrate epitopes in humans, and N-glycans with α1,6-core fucose typical for mammalian type of N-linked glycosylation. Both glycan epitopes were labelled in cryosections of salivary glands isolated from the tick Ixodes ricinus. Salivary glands secrete during feeding many bioactive molecules and influence both successful feeding and transmission of tick-borne pathogens. For accurate and reliable localization of labelled glycans in both fluorescence and scanning electron microscopes, we used carbon imprints of finder or indexed EM grids on glass slides. We discuss if the topographical images can provide information about labelled structures, the working setting of the field-emission scanning electron microscope and the influence of the detector selection (a below-the-lens Autrata improved YAG detector of back-scattered electrons; in-lens and conventional Everhart-Thornley detectors of secondary electrons) on the imaging of gold nanoparticles, quantum dots and osmium-stained membranes.
Keywords: klíště; Cryoelectron Microscopy; fluorescenční mikroskopie; uhlík; Salivary Glands; proteiny členovců; Glass; proteoglykany; Animals; Microscopy, Fluorescence; Proteoglycans; sklo; elektronová kryomikroskopie; Microscopy, Electron, Scanning; barvení a značení; zvířata; Carbon; Ixodes; Salivary Proteins and Peptides; Staining and Labeling; mikroskopie elektronová rastrovací; Arthropod Proteins; slinné proteiny a peptidy; slinné žlázy